Legalitas Hak Komunal Atas Kelestarian Hutan Adat di Wilayah Ibu Kota Nusantara (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this research is to see the influence of the legality of indigenous forests in the Capital City area, after being designated as indigenous forests by the government, on their sustainability and the factors that influence their sustainability and damage. The 1945 Constitution of The Republic of Indonesia gave responsibility to the state to manage land, water, and natural resources in Indonesia to provide maximum benefits for the people. This is explicitly stated in The Constitution and refers to the existence of Indonesian agrarian reform. Law No. 3/2022 regulated special provisions regarding land acquisition for a public purpose in the construction of the new capital city called Nusantara. The relocation of the State Capital of Indonesia has an impact on all aspects of the life of indigenous peoples in the Capital City area, especially in the land sector. This is normative legal research using statute and conceptual approaches. Some of the factors affecting public awareness of indigenous forest protection include the fact that forests have many benefits for the survival of indigenous peoples socially, religiously, economically, and culturally. Therefore, the legal protection that indigenous peoples need, such as upholding customary rights and unique life norms in the capital city's community, agreeing on zoning regulations that do not damage local cultural values ​​and eliminate public interest in the development of the State Capital, and implementing a land registration program for people who undocumented.